واقع تطبيق الادارة الالكترونية في الخدمة العمومية -دراسة حالة بلدية سيدي محمد- - يوسفي, صلاح الدين (جامعة الوادي - University of Eloued, 2022)
تعتبر الإدارة الإلكترونية أحد أهم الإستراتيجيات المتبعة قصد تحسين الخدمة العمومية وتقريب المواطن من الإدارة، وقد تناولت دراستنا هذه الإدارة الإلكترونية كآلية لتحسين الخدمة العمومية-دراسة حالة بلدية سيدي امحمد- والتي تهدف من خلالها إلى إزالة الغموض حول مفهوم الإدارة الإلكترونية ودورها في تحسين الخدمة العمومية. وبناءا على هذا قمنا بطرح اشكالية كيف تساهم الإدارة الإلكترونية في تحسين الخدمة العمومية في بلدية سيدي امحمد. وقد إعتمدنا على المقابلة التي كان فيها 18 سؤال وقمنا بتوزيعهم على 3 موظفين. وبعد تحليلنا للنتائج تطرقنا إلى أهم النتائج بأن من أسباب التحول من الإدارة التقليدية الى الإدارة الإلكترونية هو مواكبة التطورات التكنولوجية وتحديث الإدارة ومن متطلبات تطبيق الإدارة الإلكترونية هو توفير كوادر بشرية متخصصة اما غياب الدورات التدريبية من أهم العوائق الذي يواجه الإدارة الإلكترونية. Electronic management is one of the most important strategies followed to improve public service and bring citizens closer to the administration. Our study has dealt with this electronic administration as a mechanism for improving public service - a case study of the municipality of SidiM'hamed - through which it aims to remove the ambiguity around the concept of electronic management and its role in improving the public service. On this basis, we raised the problem of the contribution of electronic administration to the improvement of public service in the municipality of SidiM'hamed. We depended on the interview in which there were 18 questions and distributed them to 3 employees. After our analysis of the results, we discussed the most important results, namely that one of the reasons for the transition from traditional management to electronic management is to follow the technological evolution and to modernize the administration. The provision of specialized human
The reality of the application of electronic management in the public service Case study of the municipality of Sidi Mohamed
مقال
Keywords: الإدارة الإلكترونية؛ الخدمة العمومية.